2012
DOI: 10.1111/and.12054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol intake and cigarette smoking on sperm parameters and pregnancy

Abstract: Much has been published about smoking and alcohol intake influencing male fertility, sperm parameters and reproductive outcome. However, there is no conclusive agreement about the effects of cigarette smoking and alcohol use on these outcomes and thus no generally accepted guidelines. The combined effect of cigarette smoking and alcohol intake, though, has not been rigorously investigated. Because alcohol consumption and smoking are often seen together, this study focuses on the effect of smoking and drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
1
35
1
2
Order By: Relevance
“…It is well known from the literature that oxidative stress is considered to be the major pathological mechanism of tissue injury of the male reproductive tract occurring during cigarette smoking (de Jong et al, 2014;Zenzes, 2000) and excessive alcohol drinking (de Jong et al, 2014;Emanuele and Emanuele, 2001a). Allele 590A is part of the NAT2*6A haplotype, which causes the slow-acetylator phenotype due to producing proteins that are poorly expressed, unstable or possess reduced catalytic activities (Badawi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known from the literature that oxidative stress is considered to be the major pathological mechanism of tissue injury of the male reproductive tract occurring during cigarette smoking (de Jong et al, 2014;Zenzes, 2000) and excessive alcohol drinking (de Jong et al, 2014;Emanuele and Emanuele, 2001a). Allele 590A is part of the NAT2*6A haplotype, which causes the slow-acetylator phenotype due to producing proteins that are poorly expressed, unstable or possess reduced catalytic activities (Badawi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low fruit/ vegetable intake was found to be associated with the increased risk of infertility only in carriers of this genotype. It can be proposed that a low fruit/vegetable diet seems to (Künzle et al, 2003;Meri et al, 2013) possibly through inducing seminal oxidative stress (de Jong et al, 2014;Saleh et al, 2002). Alcohol can induce oxidative damage either by enhancing the production of highly toxic ROS from alcohol and acetaldehyde, producing lipid peroxidation of membranes in testicular cells or decreasing the concentrations of antioxidants (Emanuele et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…If a user smokes for many years or smokes many cigarettes per day, the risk for fertility problems increases (Amirkhani et al, 2014;Kim et al, 2015). However, other studies have reported that there is no significant relationship between smoking and fertility outcomes in humans (de Jong et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, inactivity and excessive fast food consumption (18,19) leading to obesity can create infertility problems, such as testicular dysfunction and reduced sperm count in males (20)(21)(22)(23), and polycystic ovarian syndrome, one of the main causes of infertility in females (24) , which most of the time can be treated through lifestyle changes (25,26). Stress, drinking alcoholic beverages, and smoking can each reduce reproductive potential through various mechanisms (13,14,(27)(28)(29)(30)(31)(32)(33). Doping, or using anabolic steroids, has the same effect as using androgens or testosterone.…”
Section: Introductionmentioning
confidence: 99%